2018
DOI: 10.4314/tjpr.v17i9.27
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based clinical study on the association of cognitive impairment with drinking and smoking

Abstract: Purpose: To evaluate the relationship between alcohol consumption and cigarette smoking among the elderly population of a Chinese city with a risk of developing cognitive decline and dementia. Methods: In this study, 1687 participants from the suburban town of Yanliang in Xi'an Sub-province, Shanxi Province, China in the age group of 60-65 years and who have not develop cognitive decline were assessed over a 6-year period. The study involved the evaluation of gender-based effect on alcohol consumption and smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“… 35 Alkhunizan et al in Saudi Arabia and Fu et al in China had similar values of 91.8% and 86.5%, respectively, of the respondents who never smoked as was seen in this study. 32 , 36 In contrast, a study by Ramlall et al in South Africa reported that 76.4% of the study population that were current smokers or ever smoked. 30 This discrepancy in smoking habits may be attributed to socio-cultural and religious differences of the different regions where the studies were conducted.…”
Section: Discussionmentioning
confidence: 91%
“… 35 Alkhunizan et al in Saudi Arabia and Fu et al in China had similar values of 91.8% and 86.5%, respectively, of the respondents who never smoked as was seen in this study. 32 , 36 In contrast, a study by Ramlall et al in South Africa reported that 76.4% of the study population that were current smokers or ever smoked. 30 This discrepancy in smoking habits may be attributed to socio-cultural and religious differences of the different regions where the studies were conducted.…”
Section: Discussionmentioning
confidence: 91%